hnRNP H binding at the 5′ splice site correlates with the pathological effect of two intronic mutations in the NF-1 and TSHβ genes - Buratti, Emanuele (Oxford University Press, 2004)
We have recently reported a disease-causing substitution (+5G > C) at the donor site of NF-1 exon 3 that produces its skipping. We have now studied in detail the splicing mechanism involved in analyzing RNA–protein complexes at several 5′ splice sites. Characteristic protein patterns were observed by pulldown and band-shift/super-shift analysis. Here, we show that hnRNP H binds specifically to the wild-type GGGgu donor sequence of the NF-1 exon 3. Depletion analyses shows that this protein restricts the accessibility of U1 small nuclear ribonucleoprotein (U1snRNA) to the donor site. In this context, the +5G > C mutation abolishes both U1snRNP base pairing and the 5′ splice site (5′ss) function. However, exon recognition in the mutant can be rescued by disrupting the binding of hnRNP H, demonstrating that this protein enhances the effects of the +5G > C substitution. Significantly, a similar situation was found for a second disease-causing +5G > A substitution in the 5′ss of TSHβ exon 2, which harbors a GGgu donor sequence. Thus, the reason why similar nucleotide substitutions can be either neutral or very disruptive of splicing function can be explained by the presence of specific binding signatures depending on local contexts.